Analisis Pengujian Pengembangan Sistem Informasi Geografis Daerah Rawan Rob Di Kota Pekalongan - Aufar, Mohammad Rasas; Raharja, Pradana Ananda (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The North Coast area of Pekalogan City is an area that has great potential for tidal flooding. Some experts say that the geographical condition of Pekalongan City has a high level of vulnerability to global warming. The high value of vulnerability is inseparable from the geomorphological conditions of Pekalongan in the form of sandy beaches and coastal erosion. Due to these conditions, Pekalongan City has become one of the areas affected by the tidal flood. The problem of tidal flooding is not a new problem for Pekalongan City, especially in the North Pekalongan part. In the design of this system will apply the agile `method. In the design of this system will apply the Agile method. In terms of software development guidelines, agile has an understanding that actively and continuously, between developers and customers must always establish good cooperation and communication. This research was conducted using a Geographic Information System (GIS). The integration of Geographic Information System (GIS) technology will provide convenience and advantages in effectively identifying, mapping, and organizing data over a large area. This study aims to make it easier for the people of Pekalongan City to identify areas prone to tidal flooding. This system can open a map of tidal flood-prone areas in Pekalongan City. Based on the results of the questionnaire calculation using a Likert scale, it can be concluded that this system has a good appearance, the layout of this system is easy to understand, this system helps in getting information about the threat of tidal waves in Pekalongan City, and this system is in accordance with what respondents expected because the percentage of index value more than 80% in each question.